Optimizing Maintenance and Repair of Central Air Conditioning on MV. Tanto Bersinar: Optimalisasi Perawatan dan Perbaikan AC Central di Kapal MV. Tanto Bersinar - Nurmala, Eka; Kusumawardhana, Enrico Putra; Sahputra, Afandi; Taharuddin; Saifudin, Iksan (PT. Alpha Trianguli Australis, 2024)
For a ship to move smoothly from one port to another, it must be supported by various types of appropriate machinery. One of them is Central AC which functions to maintain the environmental temperature around the ship at an ideal temperature so that the crew remains comfortable in their daily activities while working and resting. Therefore, a ship needs to have a cooling machine to support the comfort of the entire crew. As well as the importance of carrying out regular maintenance and repairs on the cooling machines on board the ship. This research uses a qualitative research approach, data collection techniques using direct observation, interviews and documentation or library studies. The data is processed using triangulation, the data obtained tends to be qualitative data, the data analysis is inductive or qualitative, and the results of qualitative research are to understand meaning, understand uniqueness, construct phenomena and find hypotheses. The results of this research are: 1) Factors that cause damage to Central AC so that it cannot be used properly are due to Central AC components such as dirty condensers, disconnected electrical cables, and dirty dryers as well as other factors, namely lack of accuracy in carrying out maintenance and maintenance. Central AC repair; 2) The impact that occurs when the Central AC does not work properly is a decrease in the performance of the ship's crew due to the discomfort of high room temperatures; and 3) The way to overcome problems when repairing the Central AC on a ship is that the ship's crew is on time to check, clean, maintain and repair the Central AC regularly and correctly.